2020
DOI: 10.1186/s13033-020-00381-8
|View full text |Cite|
|
Sign up to set email alerts
|

“We can’t carry the weight of the whole world”: illness experiences among Peruvian older adults with symptoms of depression and anxiety

Abstract: Background Despite the high levels of depression and anxiety symptoms in old age, the use of mental health services in this population is low. Help-seeking behaviors are shaped by how an individual perceives and experiences their illness. The objective of this study was to characterize the illness experiences of Peruvian older adults with depression and anxiety symptoms in order to lay the foundation for tailored community-based mental health interventions. Methods In this qualitative study, we conducted in-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…This scenario is based on the perception that the Divine is taking care of peoples' lives and that everything occurs according to a better purpose, even if sometimes humans cannot understand God's plan ( 37 , 178 ). This scenario was well-illustrated in the discourse of a 61-year-old Peruvian Woman examined by Flores-Flores et al ( 179 ), who explained that God was her psychologist and that she prayed to him every night to take her negative feelings away from her , and, according to her, little by little, they went away ( 179 ). In other cases, believing in the occurrence of spiritual experiences seemed to provide comfort and conciliation.…”
Section: Discussionmentioning
confidence: 89%
“…This scenario is based on the perception that the Divine is taking care of peoples' lives and that everything occurs according to a better purpose, even if sometimes humans cannot understand God's plan ( 37 , 178 ). This scenario was well-illustrated in the discourse of a 61-year-old Peruvian Woman examined by Flores-Flores et al ( 179 ), who explained that God was her psychologist and that she prayed to him every night to take her negative feelings away from her , and, according to her, little by little, they went away ( 179 ). In other cases, believing in the occurrence of spiritual experiences seemed to provide comfort and conciliation.…”
Section: Discussionmentioning
confidence: 89%
“…In the Peruvian context, the reality of retirees can be a crucial factor in uencing their mental health and suicidal ideation during hospitalization. The transition to retirement in Peru may be marked by economic, social, and adaptational challenges to signi cant changes in daily routines (39). The availability and accessibility of social security systems, as well as post-retirement socio-economic conditions, could play a fundamental role in retirees' mental health.…”
Section: Discussionmentioning
confidence: 99%
“…This is the main weakness in our research. However, some investigations such as the study of Flores et al [40] could try to answer this association. In their study, the main causes of anxiety and depression in Peruvian older adults are due to family and economic problems, loneliness, loss of independence and post-traumatic experiences [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigations such as the study of Flores et al [40] could try to answer this association. In their study, the main causes of anxiety and depression in Peruvian older adults are due to family and economic problems, loneliness, loss of independence and post-traumatic experiences [40]. Further, Failoc-Rojas et al found that older adults in another city of Peru with social problems had four times the prevalence of depressive symptoms compared to those with adequate social support [34].…”
Section: Discussionmentioning
confidence: 99%